KAJIAN INVESTASI SISTEM INFORMASI BERDASARKAN DOMAIN BISNIS PADA UNIVERSITAS X - Santoso, Leo Willyanto; Yulia, Yulia; Wirawan, Aldy (Jurnal Informatika, 2014)
Appropriate investment on information technology is needed to obtain the information technology systems that are reliable. University ' X ' has decided to do technology investments by developing academic information systems to support business processes. It is necessary to analyze the advantages and disadvantages of the systems and technology investments, and assess whether the investment has been supporting the organization's business processes . In addition, knowing the economic value of investments/ IT and ROI calculation is crucial . The purpose of the study is to analyze and assess the extent to which the success of information systems investments made ??by the company by using a business domain analysis method on Information Economics (IE). The method used was the literature research, surveys, interviews, questionnaires, documentation studies and methods of analysis. At the end of the study, it has successfully made ??the investment analysis of the University Academic Information Systems, a ROI calculation and IE Score as well as tools for storing project data and calculation results and ROI  Score